Conceptualizing the Association Between Community Participation and CQI in Aboriginal and Torres Strait Islander PHC Services. (November 2019) - Turner, Nalita Nungarrayi; Taylor, Judy; Larkins, Sarah; Carlisle, Karen; Thompson, Sandra; Carter, Maureen; Redman-MacLaren, Michelle; Bailie, Ross
Drawing from Australian Aboriginal and Torres Strait Islander perspectives, we conceptualize the association between community participation and continuous quality improvement (CQI) processes in Indigenous primary health care (PHC) services. Indigenous experiences of community participation were drawn from our study identifying contextual factors affecting CQI processes in high-improving PHC services. Using case study design, we collected quantitative and qualitative data at the micro-, meso-, and macro-health system level in 2014 and 2015 in six services in northern Australia. Analyzing qualitative data, we found community participation was an important contextual factor in five of the six services. Embedded in cultural foundations, cultural rules, and expectations, community participation involved interacting elements of trusting relationships in metaphorically safe spaces, and reciprocated learning about each other's perspectives. Foregrounding Indigenous perspectives on community participation might assist more effective participatory processes in Indigenous PHC including in CQI processes.